2000
DOI: 10.1046/j.1523-1747.2000.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Transcriptional Activity and In Vitro TNF-α Production in Psoriasis Patients Carrying the TNF-α 238A Promoter Polymorphism

Abstract: Genes encoded on chromosome 6 within the major histocompatibility complex region are thought to play an important role in the pathogenesis of psoriasis. A potential candidate gene is tumor necrosis factor alpha. The tumor necrosis factor alpha promoter contains several polymorphisms including two G-->A transitions at position -308 and -238, which are the most common in Caucasian populations. The TNF238.2 (-238A) allele has been strongly associated with psoriasis. We have investigated the effect of the -238 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
132
3
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(148 citation statements)
references
References 30 publications
6
132
3
7
Order By: Relevance
“…However, the South Croatian families analyzed in this study have not been HLA typed and therefore we can not determine whether the effects of the TNF/LTA variants are primary or secondary to HLA loci. A functional support for independent effects may be explained by transcription rate enhancement of TNF gene by TNF promoter −308 and −238 SNPs, functional control of TNF promoter SNPs on LTA expression and expression of other nearby genes [34,35,[37][38][39]. An integrated role of TNF and other inflammatory cytokines in the destruction of pancreatic beta cells [19] provides further argument for a TNF/LTA T1DM effect.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the South Croatian families analyzed in this study have not been HLA typed and therefore we can not determine whether the effects of the TNF/LTA variants are primary or secondary to HLA loci. A functional support for independent effects may be explained by transcription rate enhancement of TNF gene by TNF promoter −308 and −238 SNPs, functional control of TNF promoter SNPs on LTA expression and expression of other nearby genes [34,35,[37][38][39]. An integrated role of TNF and other inflammatory cytokines in the destruction of pancreatic beta cells [19] provides further argument for a TNF/LTA T1DM effect.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, overtransmission of A-G rs1800629(G-308A)-rs361525(G-238A) haplotype shows stronger significance (2.384×10 −5 ) than any of the single markers individually (rs1800629 (G-308A), p = 1.2×10 4 ; rs361525(G-238A), p = 8.15×0 −3 ). As both promoter polymorphisms have been associated with transcriptional enhancement rate it is possible that when acting in cis these two markers show an even stronger interaction [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Kaluza et al (2000) reported that the TNF-α-238 G allele caused a significant increase in the transcription of the TNF-α gene in human T and B cells. Thus, the effect of the TNF-α-238G allele against cancer may be conferred by an increase in TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α gene is located on chromosome 6p21.231 in the polymorphic region of MHC III, and its promoter polymorphisms have been intensively studied as a potential determinant of disease susceptibility (Kaluza et al, 2000;Gupta et al, 2008). There is also an increasing evidence that TNF-α may promote the development and spread of cancer (Liu et al, 2005;Hohberger et al, 2008;Liu et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation